2022
DOI: 10.1097/fjc.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Are High- or Low-dose SGLT2 Inhibitors Associated With Cardiovascular and Respiratory Adverse Events? A Meta-analysis

Abstract: The association between high-dose or low-dose sodiumglucose cotransporter 2 (SGLT2) inhibitors and various cardiovascular and respiratory serious adverse events (SAE) is unclear. Our meta-analysis aimed to define the association between high-dose or low-dose SGLT2 inhibitors and 86 kinds of cardiovascular SAE and 58 kinds of respiratory SAE. We included large cardiorenal outcome trials of SGLT2 inhibitors. Meta-analysis was conducted and stratified by the dose of SGLT2 inhibitors (high dose or low dose) to syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(61 reference statements)
3
8
0
Order By: Relevance
“…To date, only a few studies have investigated respiratory events associated with SGLT2is, despite its biological plausibility [ 11 ]. The lower risk of respiratory events with SGLT2is observed in the present study is consistent with prior meta-analyses that compared adverse respiratory events using data from placebo-controlled randomized trials of SGLT2is; these meta-analyses found a 25% lower risk of overall respiratory disorders [ 21 ], a 16% lower risk of pneumonia [ 22 ], a 48–60% lower risk of acute pulmonary edema [ 22 , 23 ], a 29% lower risk of respiratory failure [ 23 ], and a 41% lower risk of asthma [ 24 ]. Another trial that compared dapagliflozin versus placebo in patients with COVID-19 also hinted at potential respiratory benefits albeit showing an inconclusive lower rate of respiratory decompensation (9.3% versus 11.2%; HR 0.85, 95% CI 0.60 to 1.20) [ 40 ]; network meta-analyses in patients with diabetes and COVID-19 also suggested respiratory benefits with SGLT2is by reporting lower COVID-19 mortality [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To date, only a few studies have investigated respiratory events associated with SGLT2is, despite its biological plausibility [ 11 ]. The lower risk of respiratory events with SGLT2is observed in the present study is consistent with prior meta-analyses that compared adverse respiratory events using data from placebo-controlled randomized trials of SGLT2is; these meta-analyses found a 25% lower risk of overall respiratory disorders [ 21 ], a 16% lower risk of pneumonia [ 22 ], a 48–60% lower risk of acute pulmonary edema [ 22 , 23 ], a 29% lower risk of respiratory failure [ 23 ], and a 41% lower risk of asthma [ 24 ]. Another trial that compared dapagliflozin versus placebo in patients with COVID-19 also hinted at potential respiratory benefits albeit showing an inconclusive lower rate of respiratory decompensation (9.3% versus 11.2%; HR 0.85, 95% CI 0.60 to 1.20) [ 40 ]; network meta-analyses in patients with diabetes and COVID-19 also suggested respiratory benefits with SGLT2is by reporting lower COVID-19 mortality [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, only a small number of studies have investigated the respiratory effects of SGLT2is. Meta-analyses of randomized controlled trials showed that SGLT2is reduce the risk of adverse respiratory events versus placebo, including the risks of respiratory disorders [ 21 ], pneumonia [ 22 ], and respiratory failure [ 23 ], as well as the risk of asthma versus dipeptidyl peptidase-4 inhibitors (DPP4is) [ 24 ]. However, the respiratory effects of SGLT2is compared with other second or third-line antidiabetic drugs remain less well understood, and there is substantial uncertainty regarding the generalizability of trial findings to real-world settings [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of cardiorenal trials reported that compared with placebo, SGLT2I use was associated with a reduced risk of OAD. 19 A network meta-analysis further suggested that SGLT2I use was associated with a reduced incidence of asthma compared with dipeptidyl peptidase-4 inhibitor (DPP4I) use. 20 However, the OAD events in these trials were likely underreported, as they were extracted from reports of serious adverse events rather than being the primary end points.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent meta-analyses, which explored any possible adverse events after therapy with SGLT2 inhibitors, have shown that this drug class was associated with reduced risk of developing OSA [89,90]. In the first meta-analysis, which analysed data from 9 major studies (33,124 individuals in the SGLT2 inhibitor arm vs. 26,568 individuals in the placebo arm) found that the relative risk (RR) for experiencing OSA after their administration was 0.36 (p = 0.023) [89].…”
Section: Data From Meta-analysesmentioning
confidence: 99%
“…The second meta-analysis investigated data from 9 cardiorenal outcome studies that were stratified by 2 different doses of SGLT2 inhibitors (high or low dose); all of them had large sample sizes (ranging from 3730 to 17,160 patients). It was suggested that SGLT2 inhibitors administered either at low dose or high dose were associated with RR of 0.37 for developing OSA (95% CI: 0.17-0.81; I 2 = 0) [90]. Another meta-analysis, in which data from 9 large RCTs were analysed to evaluate the possible associations of several respiratory disorders and SGLT2 administration, suggested that SGLT2 inhibitors reduced the occurrence of OSA by 65% compared with placebo (RR = 0.35; I 2 = 0, p for treatment effect: 0.073) [91].…”
Section: Data From Meta-analysesmentioning
confidence: 99%